Determinants of Digital Consumer Behavior in Online Food Delivery Applications in the Post-Pandemic Era - Yee Huei Lok; Kok Ban Teoh; Wen Jing Cheang; Liangyu Chen; Quanxi Chen; Xinkai Feng; Zhuyi Chen; Anees Jane Ali; Daisy Mui Hung Kee (International Journal of Tourism and Hospitality in Asia Pasific, 2025)
The rapid advancement of digital technology and post-pandemic lifestyle changes have significantly transformed consumer purchasing behavior, accelerating the growth of online food delivery (OFD) platforms. This study aims to examine the factors influencing customer behavior toward FoodPanda, a leading OFD service in Malaysia, focusing on purchase decisions, usage frequency, and satisfaction. Guided by the technology acceptance model (TAM) and the theory of planned behavior (TPB), the study investigates the effects of perceived promotion, perceived convenience, perceived trust, and service quality on consumer behavior. Using a quantitative approach, data were collected from 200 respondents through an online questionnaire and analyzed using multiple regression analysis. The model explains 80.1% of the variance in customer behavior, with perceived convenience (? = 0.303) being the most influential factor, followed by perceived promotion (? = 0.276) and perceived trust (? = 0.248), while service quality (? = 0.126) is positive but weaker. The results underscore the importance of convenience, trust, and promotional strategies in enhancing customer engagement. This study provides insights into post-pandemic digital consumption patterns and offers practical implications for improving user experience and marketing effectiveness in the competitive OFD market.